Couple’s perspective on the structure and function of the family according to the period of their marriage: A field study in Hawler - Zarya Ahmed Tahir; نوری یاسین هەرزانی (QALAAI ZANIST JOURNAL, 2019)
The family is the cornerstone of society and has a great role in the socialization and formation of individual personality. Therefore, families make relations and do interaction in order to play thier roles and achieve their objectives. Family as a social system has various foundation to continue its successity and adapt its children. The purpose of this study is to identify the function and structure of the family and to know the vision of married couples on the basis of the year of marriage about the function and structure of the family, it is an analytical descriptive study in the city of Erbil. The descriptive method was used by social survey in the randomized multi-stage cluster sampling and also used the historical and comparative method. The study found that there is no signifant difference between the old and modern families in the arrangement and organization of the household affiare and relationship with their relativies, but there is a diiference between them in their perpsetive toward participating husband in daily chores